Implementasi Active Learning Dalam Pembelajaran PAI Di SMK Negeri Tegalwaru Purwakarta - Supriatna, Nana; Asy’ari, Hasyim; Zamroni, M Afif (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
This research examines the implementation of the active learning model in Islamic Religious Education at Tegalwaru State Vocational School, Purwakarta. The aim is to increase students' interest in learning, participation and achievement of learning outcomes through active involvement in the learning process. This research uses a qualitative approach with descriptive methods. Data was collected through interviews, observation and document review. The research results show that the implementation of the active learning model is carried out through three main stages: planning, implementation and assessment. In the planning stage, the teacher prepares a Learning Implementation Plan (RPP), which includes objectives, materials, activity steps and appraisal. At the implementation stage, teachers apply active learning techniques such as group discussions, debates, games and presentations to increase student participation and interest in learning. Meanwhile, the assessment stage is carried out by considering cognitive, affective and psychomotor aspects and using Minimum Completeness Criteria (KKM) as the graduation standard. The active learning model has proven to be effective in creating an interactive, fun learning environment and encouraging students to be more proactive, creative and not quickly bored in the learning process. The school also pays special attention to extracurricular activities such as recitation and billing assignments to deepen students' understanding of Islamic Religious Education. This research contributes to efforts to improve the quality of Islamic religious education in Indonesia